Insulin secretion and sensitivity after single-dose amisulpride, olanzapine or placebo in young male subjects: double blind, cross-over glucose clamp study - Kopf, Daniel; Lederbogen, Florian; Deuschle, Michael (Pharmacopsychiatry, 2012)
Increased risks of weight gain and diabetes mellitus have been reported for schizophrenic patients under long-term treatment with several atypical antipsychotic drugs including olanzapine. Among other antipsychotic drugs, treatment with the selective dopamine D2 and D3 receptor antagonist amisulpride has been implicated with a lower risk for metabolic complications. In this study we compared the acute, non-adiposity related effects of a single dose of olanzapine, amisulpride and placebo on insulin sensitivity and secretion in 10 healthy subjects in a randomised, double blind cross-over design. Subjects underwent euglycemic-hyperinsulinemic and hyperglycemic clamp tests using an automated clamp device. C-peptide and pro-insulin levels were determined using highly specific immuno-assays.Insulin sensitivity was not significantly different between both verum medications and placebo. However, C-peptide secretion during hyperglycemic clamp was significantly higher after administration of amisulpride than after olanzapine or placebo. This was true both for the early phase and for the second phase of insulin secretion (C-peptide at 0, 5,10 and 30 min: amisulpride 1.49±0.49; 4.22±1.45; 3.19±1.22; 5.33±1.85; olanzapine 1.35±0.47; 3.84±1.37; 2.72±0.91; 4.28±1.96; placebo 1.72±0.82; 3.59±1.19; 2.71±1.02; 4.54±1.42 ng/mL, mean±SD; ANOVA p=0.043). Pro-insulin levels did not differ significantly between groups. A low dose of the D2/D3 antagonist amisulpride, but not olanzapine appears to acutely increase pancreatic insulin secretion in healthy controls. Stimulation of β-cells could be a protective factor against the development of diabetes mellitus.